Effect of tartrazine dye on micellisation of cationic surfactants: conductometric, spectrophotometric, and tensiometric studies. (8th July 2016) - Ali, Anwar; Uzair, Sahar; Farooq, Ummer; Ali, Maroof
Abstract : The interactions between anionic dye (tartrazine) and cationic surfactants (dodecyltrimethylammonium bromide and cetyltrimethylammonium bromide) have been studied by conductometric, spectrophotometric, and tensiometric techniques. The conductance and surface tension of dodecyltrimethylammonium bromide and cetyltrimethylammonium bromide in pure water as well as in aqueous tartrazine when plotted with surfactant concentration gave values of the critical micelle concentration at different temperatures. As well as increasing the length of the carbon chain of surfactants, the presence of tartrazine reduces the critical micelle concentration. From specific conductivity data, the counterion dissociation constant, standard free energy, enthalpy, entropy of micellisation, surface excess concentration, surface tension at critical micelle concentration, minimum area per molecule, surface pressure at critical micelle concentration, and Gibbs energy of adsorption were evaluated. Spectroscopic studies reveal that the binding of dye to micelles brings a bathochromic shift in dye absorption spectra that indicates dye–surfactant interaction.